2015
DOI: 10.1007/s10531-015-1009-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of recreational SCUBA divers on the structural complexity and benthic assemblage of a Caribbean coral reef

Abstract: The effect of recreational SCUBA diving on coral reefs is likely secondary to many of the commonly cited stressors that threaten the long-term survival of coral reefs, such as rising temperatures. However, recreational SCUBA diving has had documented effects on various benthic organisms. Most research on the effect of SCUBA divers has focused on broken and abraded benthic organisms or the rate at which divers contact the benthos. We tested for differences in the structural complexity and benthic assemblage bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
(54 reference statements)
0
25
0
2
Order By: Relevance
“…Nonetheless, it is now clear that unregulated diving can produce serious environmental impacts, too. These include the abrasion or breakage of long‐lived sessile organisms, disturbance of fish and mammals, and altered microscale sedimentation patterns that, in the long run, can lead to community shifts (Di Franco et al , ; Luna et al , ; Bravo et al , ; Lyons et al , ). Many marine protected areas (MPAs) are favoured diving destinations and need to balance conservation with local economic ambitions.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it is now clear that unregulated diving can produce serious environmental impacts, too. These include the abrasion or breakage of long‐lived sessile organisms, disturbance of fish and mammals, and altered microscale sedimentation patterns that, in the long run, can lead to community shifts (Di Franco et al , ; Luna et al , ; Bravo et al , ; Lyons et al , ). Many marine protected areas (MPAs) are favoured diving destinations and need to balance conservation with local economic ambitions.…”
Section: Introductionmentioning
confidence: 99%
“…Spearfishing may add to local stressors on corals and other fragile benthic organisms, especially at sites with high visitation rates. Although the potential damage produced by individuals is minor, there is evidence that cumulative effects of disturbances caused by divers can have adverse effects on corals, such as loss of cover (Fava, Ponti, Scinto, Calcinai, & Cerrano, ; Hawkins et al , ) and consequently loss of structural complexity (Lyons et al, ). Injured corals are more susceptible to diseases, predation and competition interference from algae and other organisms (Guzner et al, ; Lamb et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that exhaustive pre-dive briefings and underwater interventions are two of the best and easiest ways to reduce coral damage [65,[92][93][94][95] reducing the number of contacts by 20-80% [70,93]. Similarly, Di Franco et al [80] propose to start the dives in low vulnerability habitats to give divers enough time to make their comfortable and managing with their buoyancy control.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Di Franco et al [80] propose to start the dives in low vulnerability habitats to give divers enough time to make their comfortable and managing with their buoyancy control. Supporting this approach, it has recently been demonstrated that physical contacts are more likely during the first 10 min of dives [92].…”
Section: Discussionmentioning
confidence: 99%